Groundwater flow anomalies due to an oblate spheroid - HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2008)
The paper presents exact analytical solution of the potential problem of groundwater steady flow around the oblate spheroid, buried in the uniform porous medium. The diffusity coefficients of the spheroid and surrounding medium are different. The solution is expressed in the form of general spherical harmonics in oblate spheroidal co-ordinate system. The solution for unbounded medium can be also transformed into similar problem concerning the half-spheroidal (dish-like) syncline at the surface of the Earth. There is also possible calculation of the heat flow anomaly due to disturbed groundwater flow.